A Teacher Librarian's Initiation of Literature Circles in an Elementary School: a Refleection on the Process - Anne V. Lyle (Networks: An Online Journal for Teacher Research, 2000)
Literature Circles, often called Literature Response Groups, Book Clubs and occasionally Transactional Literature Discussions, are an approach to reading instruction in which students read, write and talk about poetry, short stories and whole books. (Lyle, 1999). Through discourse students actively construct meaning by responding to a text and then by reflecting on their responses. This approach, according to Pitman (1997), "allows children to apply their natural socializing tendencies in a productive manner, making learning meaningful and hopefully internalized for additional future learning" (p. 4).